The Utilization of Artificial Intelligence (AI) in Islamic Education Administration: An Analytical Study of Implementation, Challenges, and Opportunities in Islamic Educational Institutions - Andi Azis; Ina Ristiana; Hasim Abdul Jamil (Jurnal Ilmu Pendidikan dan Sosial, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has significantly transformed various sectors, including education management. However, its application in Islamic education administration remains inadequately explored, particularly within the Indonesian context. This study aims to analyze the implementation of AI technology in Islamic educational institution administration, identify the challenges faced, and map the opportunities that arise from its adoption. This research employs a qualitative approach with a multi-site case study design, conducted at three Islamic educational institutions in Java and Kalimantan. Data were collected through in-depth interviews, participatory observation, and documentation studies involving 24 key informants comprising school principals, vice principals for administrative affairs, teaching staff, and information technology staff. Data analysis was performed using Miles and Huberman's interactive model, while data validity was tested through source triangulation and method triangulation. The findings indicate that AI implementation in Islamic education administration encompasses five main domains: student admission management, academic scheduling, student performance evaluation, document management, and teacher professional development. The study also identifies three primary challenges, namely digital infrastructure limitations, human resource competency gaps, and concerns regarding Islamic values alignment. Meanwhile, the opportunities identified include enhanced operational efficiency, data-driven decision-making, and the potential for developing AI systems grounded in Islamic values. This research contributes a novel conceptual framework designated as the "AI-Based Islamic Education Administration" (ABIEA) model, which integrates AI technology principles with the values of Islamic education management. The practical implication of this study provides a strategic reference for Islamic educational institutions in formulating AI adoption policies that are effective, ethical, and aligned with Islamic educational values.